2015
DOI: 10.5935/abc.20150055
|View full text |Cite
|
Sign up to set email alerts
|

Heart Failure with Preserved Left Ventricular Ejection Fraction in Patients with Acute Myocardial Infarction

Abstract: BackgroundThe prevalence and clinical outcomes of heart failure with preserved left ventricular ejection fraction after acute myocardial infarction have not been well elucidated.ObjectiveTo analyze the prevalence of heart failure with preserved left ventricular ejection fraction in acute myocardial infarction and its association with mortality.MethodsPatients with acute myocardial infarction (n = 1,474) were prospectively included. Patients without heart failure (Killip score = 1), with heart failure with pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…showed that those who were developed HFpEF had a 3-fold higher mortality risk than those without HF among patients with acute MI. [ 24 ] Therefore, the parameters that imply these patients would provide more accurate evidence about surveillance for sure. In the present study, LAVI/LVEFr was a significant predictor of MACE in the fully adjusted model.…”
Section: Discussionmentioning
confidence: 99%
“…showed that those who were developed HFpEF had a 3-fold higher mortality risk than those without HF among patients with acute MI. [ 24 ] Therefore, the parameters that imply these patients would provide more accurate evidence about surveillance for sure. In the present study, LAVI/LVEFr was a significant predictor of MACE in the fully adjusted model.…”
Section: Discussionmentioning
confidence: 99%
“…This is because captopril is an angiotensin-converting enzyme inhibitor that reduces ventricular filling pressure and vascular resistance. Captopril treatment after PCI can reduce left ventricular load and early myocardial remodeling, protect cardiac ejection fraction, and improve myocardial compliance and relaxation ability ( 13 ). Valsartan is an angiotensin II receptor antagonist, with the effect of dilating blood vessels to lower blood pressure, which can increase coronary perfusion in infarcted and non-infarcted areas, thereby reducing left ventricular end-diastolic pressure and reducing LVEDV and LVESV ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with acute myocardial infarction and heart failure with preserved left ventricular ejection fraction encounter elevated short-term risk and require special attention and monitoring during hospitalization. [15] Independent predictors of mortality in patients with HFpEF in different studies include older age, male gender, New York Heart Association (NYHA) class, lower LVEF, the extent of coronary artery disease, peripheral artery disease, diabetes, impaired renal function, the degree of diastolic dysfunction as assessed by Doppler echocardiography, and increased red cell distribution width Morbidity outcomes in HFrEF and HFpEF are similar. These include the rate and frequency of hospitalization for HF, symptomatic status as measured by abnormalities in myocardial oxygen consumption, six-minute walk distance, Minnesota Living with Heart Failure questionnaire scores, and other quality-oflife indicators.…”
Section: Symptomatic Patients With Hfpef)mentioning
confidence: 99%